Moderating Role of Employee Creativity between Talent Management Practices and Employee Performance: An Evidence from HealthCare Organizations in Uttarakhand (India)v - Chahar, Dr. Bhawna (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The main aim of the study is to analyze the talent management practices and its effect on employee performance and whether employee creativity moderate the relationship between talent management practices and employee performance among employees working in healthcare organizations of Uttarakhand (India).Design/Methodology: The research used descriptive research using a cross-sectional data approach. Non probability sampling technique (convenient sampling) was utilized for data collection. The sample size was 267 employees working in healthcare organizations. A well-structured questionnaire was developed for assessing the talent management practices, employee creativity and performance and was used to collect the data.Findings: Finding of this study indicates that talent management practices have substantial effect on the creativity and performance of employee. However, employee creativity also moderates the talent management practices and employee performance.Practical Implications: Present research outcome may support in designing appropriate human resource management strategies for improving performance through talent management practices and exploring means of improving employee creativity which is vital for healthcare organization. The management should develop strategies and practices for attracting talent and enhancing creativity so that employee can handle the current situation and be able to meet future need of the organization.